2020
DOI: 10.1186/s13765-019-0485-6
|View full text |Cite|
|
Sign up to set email alerts
|

Role of NADPH oxidase and its therapeutic intervention in TGF-β-mediated EMT progression: an in vitro analysis on HeLa cervical cancer cells

Abstract: Epithelial to mesenchymal transition (EMT) is a complex biological event, wherein polarized epithelial cells lose their integrity resulting in a mesenchymal phenotype with enhanced motility, a phenomenon known as metastasis. However, the underlying mechanisms of EMT are still poorly understood in cervical carcinomas. In this study, we investigated the molecular signalling events responsible for the effect of TGF-β, a potent inducer of EMT, on HeLa cervical cancer cells. We observed that TGF-β treatment (5 ng/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Thus, it enhances the invasive potential of GBM cells and their ability to invade healthy tissues [28,29]. These effects are regulated by the "secondary executors", which includes a cytoplasmic pool of connexins [30,31], and by precisely controlled gradients of reactive oxygen species [32][33][34], which play a pivotal role as migration activity modulators. Notably, EGFR signaling is also involved in bioenergetic homeostasis, contributing to metabolic reprogramming of GBM cells [35].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it enhances the invasive potential of GBM cells and their ability to invade healthy tissues [28,29]. These effects are regulated by the "secondary executors", which includes a cytoplasmic pool of connexins [30,31], and by precisely controlled gradients of reactive oxygen species [32][33][34], which play a pivotal role as migration activity modulators. Notably, EGFR signaling is also involved in bioenergetic homeostasis, contributing to metabolic reprogramming of GBM cells [35].…”
Section: Introductionmentioning
confidence: 99%
“…Previously we reported ROS-mediated EMT in TGF-β1-induced human cervical carcinoma (HeLa) cells. We also found that upon TGF-β1 treatment, among the NOX1–5 family, NOX2 and NOX4 were induced [ 28 , 29 ]. In this study, we hypothesized and confirmed that ROS might play a role in TGF-β1-induced EMT in HeLa cells through activation of the NOX pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we investigated the involvement and role of NOX in ROS-mediated EMT in human HeLa cervical cancer cells [ 28 , 29 ]. In this present study, we intended to further expand our study by analyzing the spatial-temporal distribution of NOX isoforms and its impact on redox-dependent mechanisms involving Src, FAK, integrins, MAPK enzymes, etc., in the TGF-β1-induced EMT process in HeLa cervical cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…TGF-β1 expression leads to the expression of stress-induced premature senescence (SIPS) and its senescence target genes such as fibronectin, apolipoprotein J, osteonectin and SM22. 52 Furthermore, Muthuramalingam et al 53 showed that in HR-HPV18 positive HeLa cells, the treatment with (SH2) domains that allow the phosphorylation of tyrosine residues. 54(p2) In turn, Grb2 binds to guanine nucleotide exchange factor son of seven less (SOS) through their SH3 domains.…”
Section: The Mapk Pathway In Hpv-related Cancersmentioning
confidence: 99%
“…56 Carrillo et al 57 Then, MAP2K can activate p38 isoforms (α, β, γ and δ) which activate the transcription factors: ATF-2 and Sap-1a, but deactivate growth and transcription factor DNA damage 153 (GADD45). 58 Muthuramalingam et al 53 showed that in HeLa cells, the decrease of ROS induces the downregulation of MAPK/p38 pathway. Moreover, HR-HPV16 E7 induces senescence in mouse embryonic fibroblasts (MEFs) cells by activating p38 under OS.…”
Section: The Mapk Pathway In Hpv-related Cancersmentioning
confidence: 99%